The cost efficiency effects of involuntary bank mergers : empirical evidence from Malaysia - Rossazana, Ab. Rahim; Nor Ghani, Md-Nor; Shamsubaridah, Ramlee (Faculty of Economics, Thammasat University, 2012)
Much of the merger and banking efficiency studies is centered on the market driven or voluntary merger. Thus, the uniqueness of Malaysian merger policy offers an interesting platform for this study to embark on. The merger in Malaysia is unique as all the domestic banks were enforced to merge by the government in year 1999 after years of persuasion with little success. This study attempts to quantify the impact of the involuntary merger on the cost efficiency gains over the 1990-2005 periods. Firstly, several tests have been performed to investigate whether it is best to envelope data with a common frontier of data envelopment analysis (DEA) or by separate frontiers. Secondly, this paper assesses the cost,allocative, technical, pure technical and scale efficiencies of Malaysian banking industry as the results of the merger. In general, the results suggest that the enforcement of the bank merger policy has resulted in an improvement of bank efficiency levels.